Techno-Economic Feasibility of Solar Water Heating Systems in the Winemaking Industry - José L. García; Fátima Baptista; Alicia Perdigones; Juan Lizcano; Fernando R. Mazarrón (Australian Journal of Grape and Wine Research)
The present work analyzes the feasibility of using solar water heating systems (SWHS) to supply the hot water required in the winemaking industries. The hot water demand of the sector was characterized by selecting patterns that encompass the wide range of existing casuistry. After determining the production potential of the SWHS by using an experimental system, 22500 energy simulations were carried out, combining different locations, energy prices, and prices of the necessary investment. The results demonstrate that the seasonality and irregularity of a winery’s demand pattern drastically condition the viability and profitability of SWHS. In wineries with high demand, which are relatively uniform throughout the year, the solar system with optimized design achieves energy consumption reductions between 32% (low radiation) and 52% (high radiation), with payback between 4.3 and 7.2 years. On the other hand, in wineries with highly seasonal consumption, SWHS are not profitable even in very favorable cases.